2019
DOI: 10.1371/journal.pone.0221249
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol, magnolol and its monoacetyl derivative show strong anti-fungal effect on Fusarium isolates of clinical relevance

Abstract: The antifungal activity of magnolol and honokiol, two naturally occurring hydroxylated biphenyls, and of their synthetic derivatives was evaluated on a collection of representative isolates of Fusarium oxysporum , F . solani and F . verticillioides of clinical and ecological concern. The tested compounds were proposed as a ‘natural’ alternative to conventional fungicides, even though a larger rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…[ 9 , 10 ] and Fusarium spp. [ 7 , 9 , 29 ]. The mycelial extending and biomass weight of A. alternata in our work could be strongly inhibited by up to 93.5% and 88.3% with the treatment of magnolol only at 25 μM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 , 10 ] and Fusarium spp. [ 7 , 9 , 29 ]. The mycelial extending and biomass weight of A. alternata in our work could be strongly inhibited by up to 93.5% and 88.3% with the treatment of magnolol only at 25 μM.…”
Section: Discussionmentioning
confidence: 99%
“…A number of plant extracts are considered to exert brilliant antifungal activities, including some naturally occurring polyphenols. Among the polyphenols, magnolol, extracted from the traditional Chinese herb Magnolia officinalis , showed strong antifungal activities against Fusarium species [ 7 ], Candida isolates [ 8 ], Magnaporthe grisea [ 9 ], Penicillium expansum as well as A. alternata [ 10 ]. However, little is known on its inhibitory effects against Alternaria toxins, especially AOH and AME.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that MG had similar bactericidal activity compared with fluconazole, whereas honokiol had a better effect of inhibiting the mycelium growth compared to this fungicide. Compared to terbinafine, honokiol exhibited similar antifungal activity, whereas MG was less effective at all selected concentrations ( Oufensou et al, 2019 ).…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The isomers MG (5,5′-diallyl-2,2′-dihydroxybiphenyl) and honokiol (3,5′-diallyl-4,2′dihydroxybiphenyl) are biphenyl-type neolignans. They have been recognized as the principal active components of magnolia bark extract, usually accounted for 1-10% of dry bark, depending on the Magnolia species (officinalis or obovata) and extraction method (Sarrica et al, 2018;Oufensou et al, 2019;Łata et al, 2020). Talarek et al reviewed the chemistry, bioavailability, and The studies about MG's toxicity have been done, suggesting that MG has no genotoxicity and mutagenic toxicity (Saito et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous article reporting the activity of natural phenols against clinical Fusarium spp., we observed that the percentage of growth inhibition measured in liquid medium (Vogel’s) and solid (PDA) was comparable [ 50 ]. To achieve full solubilisation of compounds 1 – 13 at 0.5 mM, the preliminary screening was carried out with a sustainable solid medium based on gellan/water, where each compound was solubilized in a 0.1% water/gellan solution.…”
Section: Discussionmentioning
confidence: 99%